Registration of 'Cara' Soft White Winter Club Wheat. Issue 1 (2nd November 2012) - Garland-Campbell, Kim; Allan, Robert E.; Anderson, James; Burke, Adrienne; Blake, Nathan; Hoagland, Chris; Walker, Carl; Chatelain, Jeron; Little, Lynn M.; Pritchett, John; Chen, Xianming; Morris, Craig; et al.
Abstract : Club wheat ( Triticum aestivum ssp. compactum ) is an important component of the export grain market for the Pacific Northwest. Our objective was to develop a club wheat cultivar with resistance to stripe rust (caused by Puccinia striiformis f. sp. tritici Westend.) and strawbreaker foot rot [caused by Oculimacula yallundae Crous & W. Gams (Wallwork & Spooner) and O. acuformis (Boerema, R. Pieters & Hamers) Crous. & W. Gams] and with the end‐use qualities that make club wheat a specialty product. The bulk pedigree breeding method was used to select 'Cara' (Reg. No. CV‐1078, PI 643435) from the cross WA7752//WA6581/WA7217 made in 1992. Cara is a semidwarf wheat with the Rht‐D1b dwarfing allele. Cara has winter hardiness equal to that of other club wheat cultivars—Bruehl, Chukar, and Coda—but less than the soft white wheat cultivars Eltan (PI 536994) or Masami (PI 634715). Cara was evaluated in multi‐environment replicated plot trials in the Washington since 2003. Grain yields were equal to or better than other club and soft white cultivars in the 30‐ to 40‐cm and the 40‐ to 50‐cm annual precipitation zones. The milling and baking quality of Cara was equal to those of the best club wheat check cultivars. Cara is resistant to all races of stripe rust prevalent since 2001, possessing Yr17 and unknown genes for stripe rust resistance. It is also resistant to strawbreaker foot rot, possessing Pch1 . Cara provides growers with an agronomically competitive cultivar with resistance to stripe rust and strawbreaker foot rot plus excellent club wheat end‐use quality.